THE IMPACT OF HAPPINESS ORIENTATIONS ON JOB SATISFACTION AMONG HEALTHCARE WORKERS: A THEORETICAL AND EMPIRICAL EXAMINATION - Bozkurt, Büşra; Demirel, Hatice Gökçe (My University, 2025)
Purpose: Healthcare workers are more likely to experience burnout, depression, drug use, and suicidal tendencies than other people. There are findings in the literature that eudaimonic (meaning) and engagement (flow) happiness orientations increase well-being and job satisfaction, and job satisfaction decreases negative job outcomes such as burnout and depression. The high rate of substance use among healthcare workers and the expectation of an increase in the future indicate a tendency toward hedonic happiness (pleasure). Therefore, the main purpose of our study is to investigate whether the happiness orientations of healthcare professionals have an effect on their job satisfaction and whether positive and negative emotions have a moderating role on this effect. Method: In this research, the 18-item scale consisting of hedonic, eudomanic and engagement dimensions created by Peterson, Park and Seligman (2005) in their study titled \"Orientations To Happiness and Life Satisfaction: The Full Life Versus The Empty Life\" was used. As a job satisfaction scale, the scale adapted to Turkish developed by Brayfield and Rothe (1951) was used. Finally, the scale to measure positive and negative emotions developed by Watson et al. (1998) were used. The analysis methods used in the research consist of arithmetic mean, reliability tests and regression analysis. The data obtained in this study were analyzed with the licensed SPSS 25 package program. Findings: Our study revealed that eudaimonic, hedonic, and engagement happiness orientations collectively accounted for 19% of the variance in job satisfaction. Specifically, it was observed that eudaimonic and engagement happiness orientations positively influenced job satisfaction, whereas hedonic happiness orientation did not exhibit a significant effect. Moreover, when investigating the moderating role of positive and negative emotions in the relationship between healthcare workers' happiness orientations and job satisfaction, it was found that positive emotions did not moderate this relationship. However, negative emotions emerged as a moderator, attenuating the strength of the relationship. In essence, our findings suggest that negative emotions diminish the impact of healthcare professionals' happiness orientations on their job satisfaction. Additionally, detailed results regarding the perception differences based on demographic characteristics are presented in the study. Result: Although the impact rate is not high, we can say that healthcare professionals prioritize the greater goals and happiness they will achieve in the future over daily pleasures and goals. Therefore, hospital managers' use of motivational resources that will highlight the contributions of healthcare professionals and the meaning they create will increase the job satisfaction of healthcare professionals. Since health problems such as burnout and depression will decrease in employees with high job satisfaction, the opportunity to provide higher quality services will increase.
Keywords: Job satisfaction; Organizational Behavior; Health Institutions Management; Healthcare worker; Happiness orientations